Sensitivity of Hepatocyte Mitochondria Transmembrane Potential to Regulation with Phenylephrine after Exposure in Dimethyl Sulfoxide and 1,2-Propanediol Solutions, and Freeze-Thawing - Malyukina, Margarita Yu.; Kavok, Nataliya S.; Borovoy, Igor A.; Averchenko, Katerina A. (Problems of Cryobiology and Cryomedicine, 2012)
Intensity of JC-1 probe aggregates fluorescence and agonist-induced changes in mitochondria transmembrane potential of rat hepatocytes prior to and after freeze-thawing were assessed by single-cell microfluorimetry. It was shown that incubation of the cells in 10% dimethyl sulfoxide (DMSO) and 1,2-propanediol (1,2-PD) solutions within an hour and the following washing decreased the fluorescence of dye aggregates. After freeze-thawing of cells with the cryoprotectants (2-step freezing down to the temperature of liquid nitrogen, thawing and washing-out the cryoprotectants) the intensity of dye aggregates fluorescence decreased down to 83 ± 6% of control in case of DMSO, and in the case of 1,2-PD the index made less than 10%. Unlike the fresh cell suspension where the rise of aggregates fluorescence intensity by 30% was found in response to short-term stimulation with phenylephrine (10-5 M) the hepatocyte suspension incubated in DMSO solution showed no response. After freeze-thawing of cells we revealed a partial recovery of their sensitivity to the hormone effect, but the response was recorded only after increasing the hormone concentration up to 10-4 M. Probl Cryobiol Cryomed 2013; 23(2):143-151.